Analysis of the Physical Condition of Monda FC Men's Futsal Players IN 2023 - M. Holis Najip (JOETAL: Journal of Education, Teaching and Learning, 2024)
The Monda FC futsal club is one of the futsal clubs located in Montong Dao Village, Masbagik Utara Baru District, East Lombok Regency, West Nusa Tenggara Province, which is one of the many futsal clubs that actively participates in futsal tournaments in East Lombok. Even though they actively practice and take part in futsal tournaments, there are still many technical things that Monda FC men's futsal players must pay attention to, namely the basic thing is the physical condition that is most dominant when playing futsal. For this reason, several things that cause the slow increase in futsal achievements include mastery of techniques, tactics, mental and physical conditions. The aim of this research is to find out the physical condition of the Putra Monda FC Futsal Players in 2023. This research is descriptive research, namely research that is solely aimed at knowing the condition of objects or events without any intention of drawing generally applicable conclusions. The population and sample in this research were 15 Monda FC futsal players. The sampling technique used in this research was Population Study. The instruments for this research are the VO2 Max endurance test, 30 meter running speed test, leg muscle strength test with the Leg and Back Dynamometer. Based on the data analysis above, the highest percentage obtained in each norm is as follows. VO2 Max the norm category is sufficient at 40%, the speed in the norm category is sufficient 40%, the leg muscle strength in the moderate norm category is 80%.